2022
DOI: 10.3390/jcm11226640
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Automated Image Processing Research Platform for Cochlear Implantation-Related Studies

Abstract: The robust delineation of the cochlea and its inner structures combined with the detection of the electrode of a cochlear implant within these structures is essential for envisaging a safer, more individualized, routine image-guided cochlear implant therapy. We present Nautilus—a web-based research platform for automated pre- and post-implantation cochlear analysis. Nautilus delineates cochlear structures from pre-operative clinical CT images by combining deep learning and Bayesian inference approaches. It ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 94 publications
1
12
0
2
Order By: Relevance
“…Recent advances in automated analysis tools such as CoreSlicer 2.0 (CoreSlicer, Montreal, QC, Canada), Innersight 3D (Innersight Labs, London, UK), Arterys (Arterys Inc., Redwood Shores, CA, USA), etc., have made it possible to conduct larger studies with more robust and reliable results, as demonstrated in a recent study on cardiac anatomy which showed the feasibility and reliability of using automated analysis tools for population studies [ 43 ]; thus, similar approaches can be applied to cochlear anatomy. This study analyzed a large number of clinical temporal bone CT images using Nautilus (v20220801; Oticon Medical [ 31 ]) to determine cochlear morphology and characteristics, making it more efficient and robust than manual measurements. Nautilus is a web-based image analysis tool that supports the automatic analysis of pre-operative surgical planning and post-operative assessment for cochlear implant procedures; additionally, ithas the potential to influence the intraoperative workflow in an augmented reality setup and to control insertion forces and trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in automated analysis tools such as CoreSlicer 2.0 (CoreSlicer, Montreal, QC, Canada), Innersight 3D (Innersight Labs, London, UK), Arterys (Arterys Inc., Redwood Shores, CA, USA), etc., have made it possible to conduct larger studies with more robust and reliable results, as demonstrated in a recent study on cardiac anatomy which showed the feasibility and reliability of using automated analysis tools for population studies [ 43 ]; thus, similar approaches can be applied to cochlear anatomy. This study analyzed a large number of clinical temporal bone CT images using Nautilus (v20220801; Oticon Medical [ 31 ]) to determine cochlear morphology and characteristics, making it more efficient and robust than manual measurements. Nautilus is a web-based image analysis tool that supports the automatic analysis of pre-operative surgical planning and post-operative assessment for cochlear implant procedures; additionally, ithas the potential to influence the intraoperative workflow in an augmented reality setup and to control insertion forces and trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…Although only the cochlear center landmark was required for further processing, using a three landmark C-MARL approach ensured better detection of the landmark [ 33 ]. CT image-detected cochlear center landmark coordinates, cochlear side and operative status for each CT image were compiled and uploaded to Nautilus (v20220801; Oticon Medical, Vallauris, France)—a web-based cochlear image analysis tool [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this observation should be relativized by the fact that for the current experiment, we used a wide range of measure-configurations and stimulation intensities in order to obtain a full-picture of the approach, but the MIC could be obtained using much fewer stimulation combinations, thereby effectively reducing the recording time to less than an hour and increasing the clinical relevance of the approach. Moreover, eABRs could be selectively used only on a subset of electrodes which would be ‘suspected’ of creating high interactions, for example, after analysis of post-images identifying ill-placed electrodes within the cochlea [ 46 , 47 , 48 ]. Further work could aim at directly comparing different electrophysiological approaches for the characterization of channel interactions in a systematic way.…”
Section: Discussionmentioning
confidence: 99%
“…The CT-scans were acquired at a resolution of 0.3 × 0.3 × 0.4 mm 3 . CT image reconstruction was performed using a web-based research platform Nautilus [ 14 ], which combines a convolutional neural network (CNN) approach with Bayesian joint appearance and shape inference for segmenting the cochlea and determining the trajectory of the electrode arrays. The angular positioning of the electrodes was determined automatically using Nautilus which extracts electrode position from postoperative CT-scan using a CNN approach and registers it with preoperative CT-scan for determining the electrode position with respect to the cochlear segmentation.…”
Section: Methodsmentioning
confidence: 99%